Iatrogenic secondary subfertility with anovulation: A case study - Banu, Jesmine; Das, Shakti; Fatima, Parveen (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3852 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):43-45